Professional Sports Facilities and Developing Urban Communities: Vancouver's Recreation Park, 1905–1912 - Mason, Daniel (Urban History Review / Revue d'histoire urbaine, 1997)
During the final decades of the nineteenth century, the city of Vancouver, British Columbia was a rapidly developing community that would become the province's dominant urban centre. This growth and prosperity would continue through the first ten years of the twentieth century, as self-made entrepreneurs would shape a city that would quadruple in size to become Canada's fourth largest metropolis. With this growth came a desire for leisure pursuits found in other established urban areas throughout North America. Thus, several local businessmen formed the Recreation Park Company Limited in 1905, which would build an athletic facility of the same name, and introduce Vancouver's first professional baseball team. Although the team would struggle through the early years of its existence, a young baseball magnate, Robert "Bob" Brown, would later purchase the team and establish a strong baseball tradition in the city. Recreation Park would also host professional lacrosse, and other prominent sporting and social events, making it a focal point for the leisure activities of Vancouver's citizens. Like Vancouver itself, the promise shown by Recreation Park would disappear. As the decade ended, new economic conditions dictated the Park's closure. Despite its brief existence, Recreation Park would have a profound effect on Vancouver's sporting community as it ushered in a new era of commercialised sport.